“Reinvent America and the World”: How Lawrence Ferlinghetti and City Lights Books Cultivated an International Literature of Dissent - Gioia Woods (European Journal of American Studies)
American poet and publisher Lawrence Ferlinghetti became a Cold War conduit for the publication and proliferation of postwar avant-garde and dissident poetry. In this essay I tell the story of how Ferlinghetti and his bookstore and press City Lights in San Francisco, California helped popularize international dissident poetry in the United States. This effort, I argue, was contingent upon the relationships Ferlinghetti cultivated with many international poets and translators between 1954-1972. From archival sources such as Ferlinghetti’s personal letters and City Lights Books records, I construct a narrative that reveals the perils and pleasures of translating, editing, and publishing dissident poetry during the Cold War.